AB0428 A systematic review on efficacy and safety of selective glucocorticoid receptor modulators in comparison to glucocorticoids in arthritis. (15th June 2017) - Safy, M; Hair, MJ De; Jacobs, JW; Buttgereit, F; Kraan, MC; Laar, JM van
Abstract : Background: Glucocorticoids (GCs) can cause unwanted effects. Both rheumatologists and patients classify osteoporosis, hyperglycemia/diabetes mellitus, cardiovascular diseases, and infections as the most worrisome adverse effects of GCs. Alternatives with less adverse effects but with good efficacy are needed, thus with a better efficacy/safety ratio. Selective GC receptor modulators (SGMRs) are designed to engage the receptor with dissociative characteristics: less transactivation of genes, mainly responsible for unwanted effects, while trans-repression of genes, inducing anti-inflammation, is maintained. Hereby, SGRMs are expected to have a better efficacy/safety ratio. A systematic review providing an overview of the efficacy and safety data of SGRMs is lacking. Objectives: To systematically review the current literature on efficacy and safety of SGRMs in arthritis, compared to those of GCs. Methods: A search was performed in Medline, Embase and the Cochrane Library, from inception dates of databases to October 5th, 2016. Experimental studies involving animal arthritis models or human material of arthritis patients, as well as clinical studies in patients of arthritis were included, if they reported original data. All types of arthritis were included. Data was extracted on the SGRM studied and on the GC as reference standard, design or setting of the study and whether or not safety and efficacy parameters had been reported. Results: A total of 437 articles was retrieved of which 15 articles were eligible for our analysis. The following SGRMs were investigated: Compound A 1–6, PF-04171327 7, LGD-5552 8–9, Compounds 4 10, 5 10, and 14 11, (R)-16 12, (R)-18 13, (R)-21 13, (R)-35 14, (R)-37 12, Ginsenoside Rg1 15 and Org 214007–0 16 . Results are shown in Table 1 . (R)-16 showed better efficacy and safety compared to prednisone. Compound A, Ginsenoside Rg 1, Compounds 14, (R)-18, and (R)-21 had better safety profiles than a GC, but with similar efficacy. (R)-35 and (R)-37 showed better efficacy than a GC, but safety data was lacking. Org 214007–0, LGD-5552, Compounds 4 and 5 and PF-04171327 showed similar efficacy as a GC, but no safety data was provided. Conclusions: Studies both assessing efficacy and safety parameters of SGRMs are scarce. Currently, there is insufficient evidence for the presumed superior efficacy/toxicity balance of SGRMs compared to that of GCs. References: Dewint P et al. J Immunol. 2008;180:2608–15. Rauch A et al. FASEB J. 2011;25:1323–32. Rauner M et al. Endocrinology. 2013;154:3719–28. Malaise O et al. Rheumatology. 2015;54:1087–92. Gossye V et al. Arthritis Rheum. 2009;60:3241–50. Gossye V et al. Ann Rheum Dis. 2010;69:291–6. Conrado DJ et al. J Pharmacokinet Pharmacodyn. 2016;43:325–41. Miner JN et al. Proc Natl Acad Sci U S A. 2007;104:19244–9. Lόpez et al. Endocrinology. 2008;149:2080–9. Yang MG et al. J Med Chem. 2015;58:4278–90. Razavi H et al. Bioorg Med Chem Lett. 2014;24:1934–40. Riether D et al. J Med Chem. 2010;53:6681–98. Harcken C et al. J ed Chem. 2014;57:1583–98. Weinstein DS et al. J Med Chem. 2011;54:7318–33. Du J et al. J Immunol. 2011;187:942–50. Van Lierop MJ et al. PLoS One.2012;7:e48385. Disclosure of Interest: M. Safy Grant/research support from: MS was supported by a research grant from Astra Zeneca. Astra Zeneca was not involved in this study., M. De Hair: None declared, J. Jacobs: None declared, F. Buttgereit: None declared, M. Kraan: None declared, J. van Laar: None declared